Robust estimation of the regularization parameter for Tikhonov filtering of natural images with circularly symmetric blurs - (:unkn) unknown (IEEE, 2005)
The frequently published MSE algorithm for image deconvolution is shown to lack robustness. The reasons for its failure is analyzed and a new version which is robust is provided.